KAJIAN TENTANG SISTEM PENGENALAN SEL DARAH PUTIH MENGGUNAKAN NEAREST FEATURE LINE DENGAN INTERPOLASI LINIER DAN SPLINE - Kelly Anthony; Arlends Chris; Lina Lina (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
The application system designed is intended to help experts in medicine to diagnose a disease by recognizing types of white blood cells. The feature lines are developed by using the linear, quadratic spline, and cubic spline interpolation methods. The results of experiments show that the development of  feature lines using linear interpolation gave better result than the spline interpolation method.Keywords : Nearest Feature Line, Principal Component Analysis, White Blood Cell, Linear, Spline.